THE EFFECT OF ETHNO-STEM E-MODULE ON STUDENTS’ LEARNING OUTCOMES - Ramadani, Putri; Diliarosta, Skunda; Muttaqiin, Arief; Evita Putri, Rahmah (Pendidikan IPA, FMIPA, UNP, 2024)
Knowing the effect of using Etno-STEM integrated science e-module learning media with Movement and Style material on students' cognitive learning outcomes is the aim of this research. The research is a quantitative type of experimental research with a Quasi Experimental method carried out with Nonequivalent Control Group Design as the research design. Taking research sample classes involves nonprobability sampling techniques with purposive sampling techniques. The variable that has an influence is in the form of an Etno-STEM integrated science e-module on Movement and Style material with student learning outcomes as the influenced variable. Data analysis uses the t test which must previously meet the prerequisite tests in the form of validity and homogeneity which is then determined from the n-gain test. The experimental class average was 71.20 and the n-gain was 0.43, while the control class average was 62.53 and the n-gain was 0.33. The results of the hypothesis test obtained a value of tcount > ttable, namely with a value of 3.37 > 2.00, resulting in H0 being rejected and H1 being accepted. So the conclusion from this data is that there is an influence of the use of Etno-STEM integrated science e-modules on student learning outcomes.